Perylene derivative dyes luminescence in polysiloxane matrix in presence of gold nanoparticles - Mantel, A.; Shautenbaeva, N.; Lang, A.; Irgibaeva, I.; Aldongarov, A.; Barashkov, N.; Mukatayev, I. (Ye.A.Buketov Karaganda State University Publishing house, 2016)
Perylene derivatives, including 1,6,7,12-tetrachlоrоperylene-3,4,9,10-tetradicarboxydianhydride (dye I) and 3,4:9,10-bis(1,2-benzimidazole)- 1,6,7,12-tetra(4-tert-octylphenoxy) perylene (syn/ anti-isomers) (dye III), were used for preparation of polysiloxane samples (PSi) containing different concentrations of gold nanoparticles (GN). Dyes I and III demonstrate significant fluorescence enhancement upon addition of GN independent on excitation energy. For Lumogen Red composition in PSi some increase of fluorescence intensity was observed upon addition of small concentrations of GN while further increase of GN concentration quenches fluorescence. The increase of Lumogen Red emission intensity which is depending on energy of excitation is probably due to increase of radiation decay rate since excitation rate decreases. Effect of GN for Lumogen Orange was expressed as quenching of fluorescence even at small concentrations of GN. Calculations at DFT level of approximation for dye III suggest location of GN in plane of perylene core for observed fluorescence enhancement.
Полисилоксан матрицасындағы перилен негізді бояғыштардың алтын нанобөлшектері қатысындағы люминесценция
Люминесценция перилен производных красителей в полисилоксановой матрице в присутствии наночастиц золота
Keywords: Perylene derivative dyes; gold nanoparticles; surface plasmon resonance; fluorescence enhancement